Vac8p release from the SNARE complex and its palmitoylation are coupled and essential for vacuole fusion - Veit, Michael (Oxford University Press, 2001)
Activated fatty acids stimulate budding and fusion in several cell-free assays for vesicular transport. This stimulation is thought to be due to protein palmitoylation, but relevant substrates have not yet been identified. We now report that Vac8p, a protein known to be required for vacuole inheritance, becomes palmitoylated when isolated yeast vacuoles are incubated under conditions that allow membrane fusion. Similar requirements for Vac8p palmitoylation and vacuole fusion, the inhibition of vacuole fusion by antibodies to Vac8p and the strongly reduced fusion of vacuoles lacking Vac8p suggest that palmitoylated Vac8p is essential for homotypic vacuole fusion. Strikingly, palmitoylation of Vac8p is blocked by the addition of antibodies to Sec18p (yeast NSF) only. Consistent with this, a portion of Vac8p is associated with the SNARE complex on vacuoles, which is lost during Sec18p- and ATP-dependent priming. During or after SNARE complex disassembly, palmitoylation occurs and anchors Vac8p to the vacuolar membrane. We propose that palmitoylation of Vac8p is regulated by the same machinery that controls membrane fusion.